Ultrasound-Assisted Extraction of Polyphenols from Pomelo (Citrus Grandis Limonia Osbeck L.) Peel - Hoang, Quang Binh; Le, Thien Trung; Ngan, Thi Kim Nguyen; Le, Nguyen Hoang Thai (JST: Engineering And Technology For Sustainable Development, 2021)
The pomelo peel occupies 50% of the fruit mass in pomelo juice processing. It contains large amounts of phenolic compounds, which may provide benefits to human health. These components should be isolated. In this study, the effects of ethanol concentrations, material-to-solvent ratios (g/mL), temperatures and sonication time on total phenolic content (TPC), naringin content and antioxidant capacity (using DPPH assay) of extract solution was evaluated. The results showed that all experimental factors significantly influenced the extraction of total polyphenol content, naringin content, and antioxidant capacity of the extract. The extraction condition was ethanol 80%, material-to-solvent ratio of 1:25 (w/v) at 60°C, and sonication time of 7.5 min, gave the extract had total phenolic content of 9.05 ± 0.08 mg GAE/g DM, naringin content of 4.65 ± 0.08 mg NE/ g DM, and antioxidant capacity of 4.76 ± 0.03 mg AAE/g DM. The ultrasound treatment was a useful method for improving the extraction of phenolic acid compounds from pomelo peel.